Tackling the Tenure Problem: Promoting Land Access for New Farmers as Part of a Climate Change Solution - Scrufari, Carrie A. (Columbia Journal of Environmental Law, 2019)
While agriculture is a main contributor to climate change, it can also be part of the solution if we can capitalize on agriculture’s mitigation potential. For example, agriculture can assist with removing carbon dioxide from the atmosphere via carbon sinks—a process called soil carbon sequestration. Through photosynthesis, plants assimilate carbon and return some of it to the atmosphere through respiration, but the remaining carbon resides in plant tissue and returns to the soil when the plants die. Experts have recognized that building the capacity of soils to continue storing carbon (through the use of cover cropping, crop rotation, and other organic practices) can be an important ally in battling climate change. Soil sequestration could substantially relieve our atmospheric impact, with some estimates predicting that soils have the capacity to mitigate climate change by matching anthropogenic emissions at an equal rate for the next forty years. Such predictions demonstrate that a key solution to climate change could include investing in and promoting local, small scale, organic, diversified farming operations that can employ climate change mitigation techniques. On the other hand, large-scale conventional agriculture that relies on monocultures and synthetic inputs causes soil degradation and thereby contributes to climate change, as degraded soils have less ability to absorb carbon. Scholars have recognized the problems embedded in the current modern industrial agricultural complex as advocates strive to promote a different system. Some argue for abandoning the conventional system of agriculture in favor of a “civic agriculture”—a system that “embodies a commitment to developing and strengthening an economically, environmentally, and socially sustainable system of agriculture and food production that relies on local resources and serves local markets and consumers.” While civic agriculture holds great promise for combatting climate change and building a healthier, more resilient food system, there are several barriers to employing such a solution. The most “widely acknowledged barrier to entry” new farmers face is access to land. If small scale, sustainable farming operations are one goal from the menu of possible climate change mitigation strategies, then the challenge of land access and the quest for achieving stable land tenure must be squarely addressed. The primary challenges that advocates face today in transitioning our food system toward a civic agriculture as part of a climate change solution is determining how to use the law to (1) promote land access and preserve farmland, (2) facilitate succession, and (3) ensure equitable and stable land tenure arrangements for new and retiring farmers. This Article explores the different legal tools that can be used to create innovative land tenure arrangements that mitigate the effects of climate change, examining such arrangements through the use of case studies. This Article seeks to disseminate information that allowed for five different successful land access arrangements in the hopes that other farmers who find themselves similarly situated might be able to replicate portions of these arrangements to become part of the climate change solution, rather than contributing to the problem. Part II of this Article discusses the legal tools—limited liability companies, leases, and conservation easements—that farmers and their advocates are using in innovative ways to preserve farmland, facilitate succession, and achieve equitable and stable tenure so that civic agriculture can play a prominent role as a partial solution to climate change. Part III examines these legal innovations in depth through the lens of five separate case studies. The Article concludes that such legal innovations are an instrumental part of responding to the challenges posed by climate change and should be replicated where possible to contribute to the welfare of robust and resilient local food systems.